EFFECT OF HEAD MANAGEMENT COMPETENCE ON TEACHER PERFORMANCE IN SMA NUSANTARA PLUS - Elysa Aryani; Alifianti Uswatun Hasanah; Hardian Dwi Putra; Zahruddin Zahruddin (JURNAL AL-TANZIM, 2021)
This study aims to determine the effect of principal managerial competence on teacher performance at senior high school Nusantara Plus. The method used in this study is quantitative. The samples in this study were all senior high school Nusantara Plus, totaling 35 people/respondents. The data collection instrument used was a questionnaire. Based on the research results on the determination test, the coefficient of determination (R square) was 0.172. The R square value of 0.172 comes from the square of the correlation coefficient or "R", which is = 0.172 or equal to 17.2%. This figure shows that the managerial competence variable (X) affects the teacher performance variable (Y) by 17.2%, and 82.8% is influenced by other variables not examined.